1991
DOI: 10.1002/jbm.820250807
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemical and mechanical effects on free radicals in UHMWPE joints during implantation

Abstract: An electron spin resonance (ESR) technique is employed to determine the free radical distribution in the articulating surfaces of retrieved acetabular cups and knee-joint plateaus (retrieved after more than 6 years of implantation). Similar measurements made on samples prepared from cyclically stressed and unstressed cups, and on samples following oxidations in nitric acid and intralipid solutions provided sufficient data to gain more knowledge about the combined chemical and mechanical effects on PE free radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 16 publications
2
46
1
1
Order By: Relevance
“…This implies that stresses alter the chemical nature of the polyethylene in these designs. A recent study has demonstrated higher levels of free radicals under the wear track of retrieved polyethylene knee components than in nonwom areas (Jahan et al 1991), which may account for the reduction in molecular weight seen in the St Georg design in this study.…”
Section: Discussionmentioning
confidence: 52%
“…This implies that stresses alter the chemical nature of the polyethylene in these designs. A recent study has demonstrated higher levels of free radicals under the wear track of retrieved polyethylene knee components than in nonwom areas (Jahan et al 1991), which may account for the reduction in molecular weight seen in the St Georg design in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Radiation stability is another common concern for aliphatic polymers, including polyolefins such as UHMWPE, which are susceptible to bond cleavage during irradiation, leading to the generation of long-lived macroradicals (often referred to as "free radicals") [66]. In contrast, because of its distinctive aromatic chemical structure, PEEK displays remarkable resistance to gamma and electron beam radiation, with G values of radical formation about two orders of magnitude lower than aliphatic polymers, such as polyethylene [67].…”
Section: Chemical Thermal and Radiation Stability: Implications Formentioning
confidence: 99%
“…24 This radical transformation can be followed by the g-factor calculated from the ESR spectra. All the UHMWPE specimens just after irradiation had a g-factor between 2.0025 and 2.0030, independent of the irradiation conditions.…”
Section: Change Of Radical Concentrationmentioning
confidence: 99%